ANTI-PHOTOOXIDATIVE EFFECT OF PHENOLIC EXTRACT FROM CLOVE PARASITE (Flower) IN SYSTEM MODEL - Wehantouw, Frenly (CHEMISTRY PROGRESS, 2008)
Clove parasite is a herbal plant commonly used in north sulawesi. Its traditionally used to cure many kindof disease, especially cancer. The objectives of this study was to determine antiphotooxidation activities ofclove parasite flower on linoleic acid 0,03 M under illuminate with 4000 lux fluoresence lamp for 5 hours.Analyses of antiphotooxidation activities based on Lee et al. (1997) method and analyses of rancidity oflinoleic acid was determine with AOCS 1990 methods. The addition of clove parasite flower extracts in thereaction mixture showed antiphotooxidation activities on linoleic acid 0,03 M. The mixture with extractshow lower peroxide value compare with control without extract after 5 hours light exposure at roomtemperature. Activities as antiphotooxidation of clove parasite extract may cause by phenolic compoundon this plantÂ Keywords: clove parasite, linoleic acid, antiphotooxdation, peroxide value